Study the Impact of Intellectual Capital on Psychological Empowerments in the Experts of Iran\'s Ministry of Youth and Sports - Omid Safari; Seyed Amir Ahmad Mozafari; Hossein Poursoltani Zarandi (Tehran University of Medical Sciences, 2017)
Background and Aim: Nowadays, organizations significantly emphasize on different aspects and dimensions of knowledge and intellectual capitals. Knowledge and information are power and each individual equipped with them is powerful. Thus attention to knowledge and intellectual capitals for reaching to Psychological Empowerments in each organization is necessary and inevitable. The aim of this research was to study the impact of Intellectual Capital on Psychological Empowerments in experts of Iran's Ministry of Youth and Sports.  Materials and Methods: This cross- sectional study was performed among 230 experts in Iran's Ministry of Youth and Sports through convenient sampling. Data collection was conducted by the use of standard questionnaires of intellectual capital Bontis (1998) and psychological empowerment Spreitzer (1995) with Cronbach's alpha coefficients of 0.71 and 0.86. Descriptive statistics and regression tests were used for data analysis by spss. Results: Results of study showed that mean intellectual capital and psychological empowerments was 3.49 and 3.81 respectively. Additionally, results showed that intellectual capital had the ability to predict the examinees' psychological empowerments (R square= 0.12). Conclusion: According to the results, it is necessary to use intellectual capitals in organizations for more psychological empowerment and also training sessions should be conduct